Treating Stage 2 Hypertension - Giles, Thomas D (J Clin Hypertens (Greenwich), 2007)
The prevalence of hypertension increases with advancing age, due primarily to increases in systolic blood pressure. Systolic hypertension is the most common form of hypertension in individuals over 50 years of age and reflects pathologic decreases in arterial compliance. Systolic blood pressure elevation is a more important risk factor for cardiovascular disease than is diastolic blood pressure elevation. Stage 2 hypertension, defined as blood pressure ≥160/100 mm Hg, is often found in older persons, who are at highest risk for cardiovascular events. In this clinical review, hypertension experts utilize a case study to provide a paradigm for treating older patients with stage 2 hypertension.